Cell-Type-Specific Transcription of Innate Immune Regulators in response to HMPV Infection - Loevenich, Simon; Malmo, Jostein; Liberg, Ann Magritt; Sherstova, Tatyana; Li, Youxian; Rian, Kristin; Johnsen, Ingvild B.; Anthonsen, Marit W. (Mediators of Inflammation, 2019)
Human metapneumovirus (HMPV) may cause severe respiratory disease. The early innate immune response to viruses like HMPV is characterized by induction of antiviral interferons (IFNs) and proinflammatory immune mediators that are essential in shaping adaptive immune responses. Although innate immune responses to HMPV have been comprehensively studied in mice and murine immune cells, there is less information on these responses in human cells, comparing different cell types infected with the same HMPV strain. The aim of this study was to characterize the HMPV-induced mRNA expression of critical innate immune mediators in human primary cells relevant for airway disease. In particular, we determined type I versus type III IFN expression in human epithelial cells and monocyte-derived macrophages (MDMs) and dendritic cells (MDDCs). In epithelial cells, HMPV induced only low levels of IFN-β mRNA, while a robust mRNA expression of IFN-λs was found in epithelial cells, MDMs, and MDDCs. In addition, we determined induction of the interferon regulatory factors (IRFs) IRF1, IRF3, and IRF7 and critical inflammatory cytokines (IL-6, IP-10, and IL-1β). Interestingly, IRF1 mRNA was predominantly induced in MDMs and MDDCs. Overall, our results suggest that for HMPV infection of MDDCs, MDMs, NECs, and A549 cells (the cell types examined), cell type is a strong determinator of the ability of HMPV to induce different innate immune mediators. HMPV induces the transcription of IFN-β and IRF1 to higher extents in MDMs and MDDCs than in A549s and NECs, whereas the induction of type III IFN-λ and IRF7 is considerable in MDMs, MDDCs, and A549 epithelial cells.